The unmet promise: a critical review of antioxidant strategies in myocardial ischemia-reperfusion injury and the path towards precision medicine - Chen, Hao; Tang, Yutao; Ren, Pan; Wu, Wenbin (Frontiers in Pharmacology, 2025)
Myocardial ischemia-reperfusion injury (MIRI) remains a major clinical challenge, with oxidative stress as a key driver. Despite extensive preclinical promise, antioxidant therapies have consistently failed in clinical translation. This critical review deconstructs this translational gap, which stems from the nuanced complexity of redox biology, inappropriate therapeutic timing, and patient heterogeneity. We argue that overcoming these hurdles requires a paradigm shift from broad antioxidant supplementation to precision medicine. This approach involves enhancing endogenous defense mechanisms, leveraging targeted drug delivery, and developing multi-modal strategies. Ultimately, integrating dynamic biomarkers, multi-omics, and artificial intelligence to tailor treatments to individual patient profiles holds the key to finally fulfilling the promise of effectively managing MIRI.